Evaluasi fungsi kemas ulang informasi berbasis kecerdasan buatan di perpustakaan perguruan tinggi - Irkhamiyati, Irkhamiyati (Daluang: Journal of Library and Information Science, 2025)
Purpose. Artificial Intelligence (AI) holds great potential for repackaging information in academic libraries, particularly for historical physical collections. Each library must align its information management strategies with institutional development, as seen in the Library of Universitas 'Aisyiyah Yogyakarta (UNISA), which has evolved from a Midwifery School into a university. Two special collections in this library were evaluated to assess the effectiveness of AI-based information repackaging. This evaluation is important to ensure that resource utilization aligns with the outcomes achieved. The study aims to identify the functional value of AI-based repackaging for these collections. Methodology. This descriptive qualitative study was conducted from September to October 2024 at the UNISA Yogyakarta Library. A purposive sampling method was used to obtain in-depth interviews from three informants based on their fields of expertise. Data were collected through observation and interviews. Data analysis included needs analysis, design proposal, data reduction, data presentation, and conclusion drawing. Data validity was tested using time triangulation and confirmability techniques. Results and discussion. The results of the study show that most of the AI-based information repackaging functions at the UNISA Yogyakarta Library have fulfilled their functions. However, there is one function that has not been fulfilled, namely as a medium that accelerates the application of research or research results. Conclusions. While the majority of AI-based information repackaging functions have been successful, efforts are still needed to enhance its role in disseminating and applying research results. Strategic development, inter-unit collaboration, and stronger technology integration are recommended to optimize these services.